Artemis : a novel - Weir, Andy (Crown, 2017)
"Jasmine Bashara never signed up to be a hero. She just wanted to get rich. Not crazy, eccentric-billionaire rich, like many of the visitors to her hometown of Artemis, humanity's first and only lunar colony. Just rich enough to move out of her coffin-sized apartment and eat something better than flavored algae. Rich enough to pay off a debt she's owed for a long time. So when a chance at a huge score finally comes her way, Jazz can't say no. But engineering the perfect crime is just the start of her problems--because her little heist is about to land her in the middle of a conspiracy for control of Artemis itself. Trapped between competing forces, pursued by a killer and the law alike, she'll have to hatch a truly spectacular scheme to have a chance at staying alive and saving her city. Jazz is no hero, but she is a very good criminal. That'll have to do"--Back cover.